Phase change and electrical characteristics of Ge-Se-Te alloys - Lee, Eui-Bok; Ju, Byeong-Kwon; Kim, Yong-Tae (ELSEVIER, 2009)
Effects of Se contents in Ge-Se-Te ternary systems are investigated using edge contact type phase change random access memory cell structures. Increasing the Se content from 6 to 35 at% crystallization temperature and Ovonic switching threshold voltage are increased due to the large grain growth of hexagonal microstructure in the Ge-Se-Te alloys. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: MEMORY; CRYSTALLIZATION; SB